2008
DOI: 10.1177/1077558708328815
|View full text |Cite
|
Sign up to set email alerts
|

Review: Review of Nurse Home Visiting Interventions for Community-Dwelling Older Persons With Existing Disability

Abstract: Despite there being a considerable number of meta-analyses and reviews synthesizing the nurse in-home visiting literature, there have been no reviews examining nurse in-home visiting for patients who are already disabled. This article presents a literature review and synthesis of 10 trials targeted on older adults with disability. The review is organized into structure and process components related to the outcome variable disability based on the classic Donabedian model. The review suggests that the component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 62 publications
4
55
1
3
Order By: Relevance
“…They recognised the importance of nurse-patient relationships in successful interventions, as this enabled professionals to tailor interventions to patients' individual needs. 22 Implications for future research Studies on home visits have shown inconsistent results. Home visits in these studies especially focused on cure and prevention.…”
Section: Provenancementioning
confidence: 99%
“…They recognised the importance of nurse-patient relationships in successful interventions, as this enabled professionals to tailor interventions to patients' individual needs. 22 Implications for future research Studies on home visits have shown inconsistent results. Home visits in these studies especially focused on cure and prevention.…”
Section: Provenancementioning
confidence: 99%
“…Prior research has demonstrated that multiple barriers exist to intervention delivery in HHC interventions due to the complexity of the home environmental as well as the changing social milieu (Liebel, Friedman, Watson, & Powers, 2009;Markle-Reid et al, 2014). For example, one study (Nicolaides-Bouman et al, 2007) found that patients were less likely to engage in collaborative self-care management with nurses when there were contextual challenges such as unsafe home environments or cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…However, evaluations of the effectiveness of proactive home visit programs in systematic literature reviews and meta-analyses yield inconsistent results: Some individual studies report positive effects on patient outcomes such as functional status, mental health, and perceived social support, whereas others find no results at all (Elkan et al, 2001; Hoogendijk, 2016; Huss et al, 2008; Marek & Baker, 2006; Markle-Reid et al, 2006; Stuck et al, 2002). So far, this inconsistency remains poorly understood: Differences in study design, program characteristics, target populations, and context complicate the investigation of what program components contribute to a change in outcomes (Huss et al, 2008; Liebel et al, 2009; Markle-Reid et al, 2006). In addition, little information exists about how aspects of the care process (such as implementation, quality of delivery, and the extent to which care is tailored) influence program impact.…”
Section: Introductionmentioning
confidence: 99%